Firm behaviour and public infrastructure - The Case of Hungary - Gabor Bekes; Balazs Murakozy (Hungarian Academy of Sciences, Institute of Economics, 2005)
In the paper, we test the effect of local development, regional and local policies on the location decisions and productivity of firms. Development indicators include local research and development activity or education while policy decisions used in this study encompass for example tax rates, investment incentives or road construction. The study builds upon a large national panel of firms. Importantly, such a rich dataset has rarely been employed for productivity and location choice exercises. The paper is composed of two sections dealing with location choice and productivity, respectively and we compare the effect of variables used in both sections. Among others, we find that density of road network positively influenced location choice and productivity as well, while a somewhat larger size of administration helps new firms to settle but later on, it has no effect on productivity.
Keywords: R3; R12; D24; H7; C30; C35; 330; industrial location; FDI; productivity; discrete choice mod-els; GMM